A Framework Of Next Generation Adaptive CNC Controller - Othman, Muhammad Azri; Minhat, Mohamad; Jamaludin, Zamberi (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Modern manufacturing industries have increasingly demanded to bring comprehensive input data described using high-level languages such as STEP-NC, rather than outdated G&M codes into computer numerical control machine tool levels. In current dynamic shop floor environments, predefined numerical control (NC) command generated in early stages is regularly found unusable or unsuitable for the dedicated resources, causing useless efforts used up in the initial process planning and NC code generation. This research aims to propose a new structure of an adaptive CNC controller by taking the advantages of well-known IEC61499 and STEP-NC standards.For realising adaptive CNC controller capability, integration of the native process planning decision-making function into CNC controller will be established. The activities such as cutting tool selection, machining parameter determination and toolpath generation will be issued automatically by the controller itself that subject to available online machine resources. The generic STEP-NC file is employed as data input and arranged accordingly in the IEC 61499 function block software editor. The system is developed in the JAVA environment by using proposed language.